Withdrawing incentives to attract FDI: Can host countries put the genie back in the bottle? - Anna De Luca (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2014)
While generous national incentive schemes may help attract FDI, the withdrawal of incentive schemes or subsequent changes thereto affecting foreign investors might be challenged under IIAs, with host countries facing the risk of being overwhelmed with investment arbitration claims.
Keywords: 330